International public administration on the tip of the tongue: Language as a feature of representative bureaucracy in the economic community of west African states - Murdoch, Z., Gravier, M. and Ganzle, S. (International Review of Administrative Sciences)
Recent scholarship shows increasing interest in gender, ethnic or national representation within regional and international organizations. In contrast, language as a criterion of representation has rarely been scrutinized. We argue that this constitutes an important oversight for two reasons: (1) language is an important identity marker; and (2) language regimes in international public administrations can uniquely address representativeness relative to both member states and groups of citizens. Our article explores language representation in the Economic Community of West African States, and pursues a twofold objective: first, it extends the applicability of representative bureaucracy theory to the issue of language; and, second, it broadens the scope of representative bureaucracy studies by providing the first study on a prominent West African regional organization. As such, we develop avenues for future research on other regional and international organizations.- Reproduced
Keywords: Economic community of West African states, Language, Regional Organisations, Representative bureaucracy